PENYULUHAN DAN PEMBERIAN MAKANAN TAMBAHAN BERBAHAN DASAR TEPUNG DAUN KELOR PADA BALITA DI POSYANDU TERATAI DESA MANGKURAKYAT - Tri Wahyuni; Desy Syswianti; Fitri Hanriyani; Rosita Alvia; Naning Suryani; Sela Windi Suciati (LP4M STIKes Karsa Husada Garut, 2021)
Stunting is still a big challenge faced by the Indonesian people. Although the national stunting rate has decreased from 37.2% in 2013 to 30.8% in 2018, this figure is still below the WHO recommendation, which is <20%. Stunting occurs due to malnutrition, especially in the first 1000 days of life. Adequate nutrition is needed to avoid or minimize the risk of stunting. Utilization andprocessing of Moringa leaves to prevent and overcome stunting has not been widely carried out in Indonesia due to the lack of public knowledge about the benefits of Moringa leaves for health. This service activity aims to introduce parents to the benefits of Moringa leaves to prevent stunting in toddlers. The method of activity is carried out in the form of counseling and providing additional food for toddlers. The activity was held at the Lotus Posyandu, Mangkurakyat Village, Garut Regency on Wednesday, November 24, 2021 and was attended by 47 participants. The knowledge of parents of toddlers increased after being given counseling about the benefits and utilization of Moringa leaves.